The expansion of the middle and rich classes heterogeneously intensifies regional water withdrawal in China - Fanghui Zhang; Liyuan Wei; Yuanchao Hu; Hua Yan; Huwei Cui; Chang Chen; Zhen Wang (Resources, Environment and Sustainability, 2023)
China’s population–income structure has undergone significant changes. However, the impact of population expansion and changes in consumption patterns of specific income groups on regional water withdrawal has not been quantitatively assessed. Here we incorporate multiregional input–output (MRIO) tables with national survey data to capture the water footprint (WF) in the consumption of each income group in China by considering each group’s consumption patterns and population changes. The results show that the middle and rich classes contributed 83% (2012) and 89% (2015) of embodied water withdrawal, respectively. Among the driving factors leading to changes in water withdrawal, changes in consumption patterns and the population–income structure led to increases of approximately 15.4 billion m3and 12.4 billion m3, respectively. Households on the East Coast (EC), and South Coast (SC), as well as in Central China (CC), and Southwest (SW) were the key contributors to the increase. Our findings highlight essential water conservation policies to consider to meet the needs of transforming society.